Gothic television - Wheatley, Helen (Helen M.) (Manchester University Press, 2017)
Analysing key programmes - from 'Mystery and Imagination' and 'Dark Shadows' to 'The Woman in White' and 'Twin Peaks' - this text looks at the appearance of the gothic on television, uncovering an aspect of TV drama history which has remained critically unexplored.
Available through ManchesterHive.
Keywords: Horror television programs -- Great Britain -- History and criticism.; Horror television programs -- United States -- History and criticism.; Émissions d'horreur télévisées -- Grande-Bretagne -- Histoire et critique.; Émissions d'horreur télévisées -- États-Unis -- Histoire et critique.; Popular Culture.; SOCIAL SCIENCE / Popular Culture.; PERFORMING ARTS / Television / History & Criticism; Horror television programs; Great Britain; United States; Criticism, interpretation, etc.